Choice of activation protocol impacts the yield and quality of CAR T cell product, particularly with older individuals - Palak H Mehta; Gemma S Trollope; Patrick Leung; Shivali Savita Chinni; Anna Iasinskaia; Aaron J Harrison; Hannah Hughes‐Parry; Misty R Jenkins; Michael H Kershaw; Anthony Jaworowski; Clare Y Slaney; Rachel M Koldej; et al. (Clinical & Translational Immunology)
Abstract Objectives In clinical chimeric antigen receptor (CAR) T cell therapy, one of the strongest correlates of favorable patient responses is lower levels of differentiation in T cells from the peripheral blood mononuclear cell (PBMC) starting material or the CAR T cell product. T cells from older patients are inherently more differentiated, but we hypothesised that specific activation protocols could be used to limit CAR T cell differentiation during manufacturing, particularly in older patients. Methods We used PBMCs from young (20–30 years old) and older (60+ years old) healthy donors to generate CAR T cells using two activation protocols: soluble anti‐(α) CD3 monoclonal antibody (mAb) vs immune complexes of αCD3 and αCD28 mAbs. Products were assessed for yield, function and differentiation, which was used as a measure of CAR T cell quality. T cells in PBMCs were assessed for CD28 expression and correlative analyses were performed. Results Older samples generated fewer, more differentiated CAR T cells than young samples, and the αCD3/CD28 mAb protocol exacerbated this, further reducing yield and quality. CD28 expression by T cells correlated with CAR T cell differentiation, but T cell differentiation in PBMC starting material was a stronger correlate of CAR T cell differentiation. Conclusions Choice of activation protocol can substantially impact on the yield and quality of CAR T cells during manufacturing. This is a key consideration for older patients whose samples already generate a poorer yield and lower quality of CAR T cells.